LEAP-based energy demand and emissions modelling for low-carbon transport in Khon Kaen province, Thailand - Kullayawan Woraratch; Pongrid Klungboonkrong; Atit Tippichai (International Journal of Renewable Energy Development, 2026)
Climate change mitigation in Thailand requires urgent transformation of energy-intensive sectors, notably transport in rapidly urbanizing provinces. Khon Kaen, a central economic hub in northeastern Thailand, faces increasing energy demand and transport-related greenhouse gas (GHG) emissions driven by rising private vehicle ownership and limited public transit integration. This study applies the Low Emissions Analysis Platform (LEAP) to model long-term energy demand and GHG emissions under two scenarios: Business-as-Usual (BAU) and Low-Carbon Scenario (LCS). A bottom-up vehicle stock turnover approach was combined with socioeconomic projections to simulate transport energy consumption from 2024 to 2050. The LCS integrates electric vehicle (EV) promotion, expansion of Light Rail Transit (LRT), Double-Track Rail (DTR) and High-Speed Rail (HSR), and implementation of Transit-Oriented Development (TOD) strategies. Results show that, compared with BAU, the LCS can reduce transport-related GHG emissions by 62.9% by 2050 and final energy demand by 43.5%, reflecting a substantial shift from fossil fuels toward electricity and biofuels. Under the LCS, adoption of EVs is projected to reach 100% of new passenger car sales by 2050, supported by the electrification of rail transport and decreased Vehicle Kilometres Travelled through TOD-based planning. These findings confirm that locally calibrated, integrated transport and land-use measures can significantly support Thailand’s national targets for carbon neutrality by 2050 and net-zero emissions by 2065. The modelling framework may potentially transferable to other mid-sized cities and provides evidence-based guidance for low-carbon urban transport planning.